2018
DOI: 10.1038/s41386-018-0018-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COMT genotype and tolcapone on lapses of sustained attention after sleep deprivation in healthy young men

Abstract: Tolcapone, a brain penetrant selective inhibitor of catechol-O-methyltransferase (COMT) devoid of psychostimulant properties, improves cognition and cortical information processing in rested volunteers, depending on the genotype of the functional Val158Met polymorphism of COMT. The impact of this common genetic variant on behavioral and neurophysiological markers of increased sleep need after sleep loss is controversial. Here we investigated the potential usefulness of tolcapone to mitigate consequences of sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 62 publications
1
32
0
Order By: Relevance
“…To examine the impact of the genetic haplotype of AQP4 on the sleep EEG, we investigated data from 134 healthy participants of six previously published sleep deprivation studies (28)(29)(30)(31)(32)(33) All studies were conducted under strictly controlled conditions in the sleep lab of the Institute of Pharmacology and Toxicology at the University of Zürich, Switzerland using similar protocols and methodology ( Figure 1E). Two carriers of rare haplotypes as well as 9 older participants with an age above 60 years were excluded from the analysis.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…To examine the impact of the genetic haplotype of AQP4 on the sleep EEG, we investigated data from 134 healthy participants of six previously published sleep deprivation studies (28)(29)(30)(31)(32)(33) All studies were conducted under strictly controlled conditions in the sleep lab of the Institute of Pharmacology and Toxicology at the University of Zürich, Switzerland using similar protocols and methodology ( Figure 1E). Two carriers of rare haplotypes as well as 9 older participants with an age above 60 years were excluded from the analysis.…”
Section: Study Populationmentioning
confidence: 99%
“…The No difference in the distribution of the AQP4-haplotype between the six studies was observed (p > 0.21). In studies that included the administration of one or more treatments (28)(29)(30), only data from the placebo-arm were analyzed.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We next assessed whether humans showed a similar heterogeneity in the response of δ power to SD. A total of 110 healthy human subjects from four published datasets who underwent wholenight SD amounting a sustained waking period of 40h (Bodenmann et al, 2009, Holst et al, 2017, Valomon et al, 2018, Weigend et al, 2019, were included in the analysis. Here we show only the aggregate results, but similar results were obtained in each study separately.…”
Section: Distinct δ Sub-bands Are Present In the Human Brain Followinmentioning
confidence: 99%
“…All subjects signed informed consent and were compensated financially for participating. For more details see previous publications (Bodenmann et al, 2009, Holst et al, 2017, Valomon et al, 2018, Weigend et al, 2019. Some subjects were removed across 5 studies for signal artifacts, which made time-course analysis of spectral bands difficult.…”
Section: Study Participantsmentioning
confidence: 99%